Practising history selected essays - Tuchman, Barbara (Barbara Wertheim) (Papermac, 1983)
From thoughtful pieces on the historian's role to striking insights into America's past and present to trenchant observations on the international scene, Barbara W. Tuchman looks at history in a unique way and draws lessons from what she sees. Here is a splendid body of work, the story of a lifetime spent "practicing history."